2007
DOI: 10.1002/hyp.6608
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seasonal local recharge using electrical resistivity tomography and magnetic resonance sounding

Abstract: International audienceA groundwater recharge process of heterogeneous hard rock aquifer in the Moole Hole experimental watershed, south India, is being studied to understand the groundwater flow behaviour. Significant seasonal variations in groundwater level are observed in boreholes located at the outlet area indicating that the recharge process is probably taking place below intermittent streams. In order to localize groundwater recharge zones and to optimize implementation of boreholes, a geophysical survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 34 publications
1
74
0
1
Order By: Relevance
“…These systematic changes cannot be explained or related to any natural process. Descloitres et al (2003Descloitres et al ( , 2008b showed with synthetic data that time lapse inversion may produce artifacts due to the smoothness constraints especially with changes caused by shallow infiltration (decrease of resistivity), as mostly expected in our case.…”
Section: Ert Data Inversionsupporting
confidence: 79%
See 1 more Smart Citation
“…These systematic changes cannot be explained or related to any natural process. Descloitres et al (2003Descloitres et al ( , 2008b showed with synthetic data that time lapse inversion may produce artifacts due to the smoothness constraints especially with changes caused by shallow infiltration (decrease of resistivity), as mostly expected in our case.…”
Section: Ert Data Inversionsupporting
confidence: 79%
“…However, some research has been conducted under natural conditions to characterize water content change, infiltration or discharge by use of cross-borehole ERT (French and Binley, 2004), surface ERT (Brunet et al, 2010;Benderitter and Schott, 1999;Descloitres et al, 2008b;Massuel et al, 2006;Miller et al, 2008) or a combined surface cross-borehole ERT array (Beff et al, 2013;Zhou et al, 2001).…”
Section: R Hübner Et Al: Monitoring Hillslope Moisture Dynamics Witmentioning
confidence: 99%
“…They demonstrated using synthetic models that infiltration processes at shallow depths usually produce a decrease in resistivity in the upper layer, while an increase in resistivity may be observed at intermediate depths, where the resistivity is actually not changing. 850 Descloitres et al (2008) identified such time-lapse artefacts, when tracking seasonal recharge processes by ERT, especially located in the subsurface of slopes. These studies point out that infiltration through a succession of layers with different resistivity signatures may enhance such artefacts.…”
Section: 23mentioning
confidence: 99%
“…Electrical Resistivity methods have been widely used for surveys where the sub-surface resistivity is heterogeneous and can provide valuable information regarding bed rock geometry [1]. Electrical Resistivity is a function of the water content in the subsurface strata, the porosity of the geologic material, the electrical conductivity of water, the rock type an temperature, [2][3][4].…”
Section: Methodsmentioning
confidence: 99%